It can not be factored because its discriminant is less than zero
X2 - 8X + 15 = (X - 3)(X - 5)
x^2 +8x -9 is equivalent to (x+9)(x-1) when factored
(x + 4)(x +4) or (x + 4)squared
Find out what two numbers add up to -8 yet when mutiplied they produce 12 and so: x squared-8x+12 = (x-2)(x-6) when factored
8x2-39x+45 = (8x-15)(x-3) when factored
(x - 6)(x - 2)
18 + 8x + x = = 18 + 9x = 9(2 + x) which is the factored form of the expression.
This is not factor-able.
Y-8x plus 9y equals 10y-8x.
(x-3)(x-5) = 0
8x plus 4y equals 5 is 8x + 4y = 5.
The given expression can be simplified to: 8x squared +9
It is: 25+64 = 89
5 - 8x + 3x2 = 3x2 - 8x + 5 (since the sign of the second term is negative, then 5 can be factored as (-1)(-5)) = (3x - )(x - ) (try to put 1 or 5 to the empty places, in order to obtain -8x) = (3x - 5)(x - 1)
the answer of √8x+16-3x=0 is x= 0.447213595 = +/- 0.447(to 3 decimal places) if I'm not mistaken
x2-8x+16 = (x-4)(x-4) when factored
- 8x + 8x = 0 so question is meaningless.
x^2-8x+3 This expression cannot be factored as (x+a)(x+b) where a and b are integers. This is because you cannot find two integers such that their sum is -8 and product 3.
8x-7 plus 2x equals 6 plus 5x plus 2?
6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.